Global virtual teams coordination mechanisms: building theory from research in software development. Issue 9 (4th July 2022) - Kiely, Gaye; Butler, Tom; Finnegan, Patrick
ABSTRACT: The advent of globalisation has led to the growing use of global virtual teams (GVT) for software development. The use of such teams enables organisations to operate across national, economic and social, and cultural boundaries; this new form of teamwork presents challenges for traditional coordination mechanisms. Hence, a range of new operational problems for the coordination of software development teams have emerged due to the nature of virtual work: these are related to issues of geographical distance, language differences, time zone(s) differences, cultural differences, and trust. This paper applies a theoretical model drawn from prior research to explore the coordination mechanisms employed by a global virtual software development team in a major multi-national telecommunications organisation. The study analyses the impact that the aforementioned issues have on the effectiveness of project team coordination mechanisms and then develops a refined conceptual model to guide future research on global virtual software development teams. The findings also inform practice on the problems encountered in ensuring the effective coordination of such teams.